Management of the Development of Project Modules For Strengthening The Profile of Independent Learning-Based Pancasila Students In Phase E At Doloksanggul State Special School - Sinabutar, Fernan; Samosir, Lustani; Sitompul, Arip Surpi (the International Journal of Education, Theology, and Humanities, 2025)
This research aims to develop and evaluate the project module strengthening the profile of Pancasila student based on Merdeka Belajar for phase  E in SLB Negeri Doloksanggul, with a mangement approach using the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). This research focuses on four main aspects: 1) the stages of module development; 2) the conten and language validyty of the module; 3) thpracticality of using the module by teacher and students; 4) the effectiveness of the module in improving leearning outcomes. The results showed that the develop module had gone through the ADDIES stages systematically and was declared valid, with a validation score from the material expert of 4,81 and the linguist of 4,84. The module also proved to be very pratical to use, indicated by the teacher’s ability to manage learning with a average score of 4,74, as wall as the active involvement of students in accordance with the ideal time indicators of learning activities. In terms of effectiveness, the module showed fery satisfactory results. All students (100%) achieved learning completeness with an average score of 92,78, and students gave positive responses to the use of modules in project learning. Thus, this project module can bie used as an alternative innovative and inclusive learning strategy in strengthening the character and competence of Pancasila students in the SLB enviroment.